Synthesis of Biologically Active 1-[2-(2-Methyl- 5-nitroimidazol-1-yl)acetyl]-3-substituted Phenyl-4-carbaldehyde-1H-pyrazoles - H. HAVALDAR, FREDDY; R. PATIL, ABHAY (Asian Journal of Chemistry, 2010)
1-[2-(2-Methyl-5-nitroimidazol-1-yl)acetyl]-3-substituted phenyl- 4-carbaldehyde-1H-pyrazoles (4a-e) have been synthesized by the cyclization of (2-methyl-5-nitroimidazol-1-yl)acetic acid (1-substituted phenylethylidine)hydrazides (3a-e) with phosphorous oxychloride in N,N-dimethylformamide. The pyrazoles have been characterized on the basis of analytical and spectral data and screened for biological activity.